2021
DOI: 10.21203/rs.3.rs-144175/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selenium-Related Nutritional Status in Patients With Common Variable Immunodeficiency: Association With Oxidative Stress and Atherosclerosis Risk

Abstract: Background: Common variable immunodeficiency (CVID) is an innate immunity error, possibly associated with recurrent or chronic infections and autoimmune / inflammatory diseases and neoplasms. It is suggested that these conditions lead to persistent immune stimulation and increased oxidative stress. A positive impact on the survival of patients with an inborn errors of immunity was observed with advanced clinical care protocols, thus raising concerns about the risk of developing other associated chronic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Recent research has demonstrated that patients with CVID (common variable immunodeficiency) had considerably lower levels of plasma selenium and GPX activity than healthy controls [150]. Se level, apolipoprotein A-1 concentration, and the main proteins that make up the highdensity lipoprotein cholesterol component all showed a substantial positive association.…”
Section: Seleniummentioning
confidence: 99%
“…Recent research has demonstrated that patients with CVID (common variable immunodeficiency) had considerably lower levels of plasma selenium and GPX activity than healthy controls [150]. Se level, apolipoprotein A-1 concentration, and the main proteins that make up the highdensity lipoprotein cholesterol component all showed a substantial positive association.…”
Section: Seleniummentioning
confidence: 99%
“…Selenium (Se) is an essential trace element for all animals including humans and is important for physiologic functions and has extensive pharmacological effects (Avery & Hoffmann, 2018). Selenium plays an important role in the treatment and prevention of adverse blood lipid profiles (Ju et al., 2018), inflammation and immune‐related diseases (Andrade et al, 2021; Avery & Hoffmann, 2018), coronavirus infections (Moghaddam et al., 2020), cancer (Hatfield et al, 2014; Vinceti et al., 2018), and Parkinson's disease (Ellwanger et al., 2016). The main source of Se intake for humans is food.…”
Section: Introductionmentioning
confidence: 99%